TB and COVID-19: paying attention to diabetes mellitus. (27th February 2021) - Harries, Anthony D; Kumar, Ajay M V; Satyanarayana, Srinath; Lin, Yan; Dlodlo, Riitta A; Khogali, Mohammed; Zachariah, Rony; Kapur, Anil
Abstract: In 2019, global diabetes prevalence was 463 million. Diabetes increases the risk of TB and adverse treatment outcomes including death and relapse. Diabetes also increases the risk of severe disease, multi-organ failure, coagulopathy and death in COVID-19. TB and COVID-19 share many features, suggesting opportunities to integrate prevention, diagnosis and care. Three areas for further work are highlighted: better infection control in diabetes clinics, easier and quicker diagnosis using similar technology platforms and optimal blood glucose control. The funding and resources for COVID-19 should be harnessed to improve TB and diabetes care and achieve their respective sustainable development goal targets.